El recuerdo como un problema del espacio pictórico en los paisajes de Patricio Larrambebere (2016)
This article aims to study about memory configuration in Patricio Larrambebere´s landscape paintings that were produced during the last years of the 90s. From the analysis of these works, my proposal is to realize about tensions which these paintings produce to its contemporary time. Considering these works are made in a historical moment marked by the development and expansion of a neoliberal culture, which reconfigures the socials practices and public spaces of Buenos Aires and its surroundings. The works selected for this article shows: a) an emphasis on painting as work and also as a document; b) the gradual disappearance of the human figure; and c) a process of abstraction that affect the paintings. I consider that these aspects contributed to the creation of a contemporary historical painting. The use of this kind of painting is an action against the uneasiness that produces the imminent loss of a public space and a historical subject in crisis. In this context, the act of painting manifests an effort in order to keep a space of experience which was desappearing at that time. This loss is related with the last traces of the Welfare State in the country. This situation explains the figurative precariousness which the artist used to represent different social emblematic buildings and landscapes such as clubs, railway stations, cinemas, radios or traditional markets.